Probiotics importance and their immunomodulatory properties. Issue 6 (14th October 2018) - Yousefi, Bahman; Eslami, Majid; Ghasemian, Abdolmajid; Kokhaei, Parviz; Salek Farrokhi, Amir; Darabi, Narges
Abstract: Mammalian intestine contains a large diversity of commensal microbiota, which is far more than the number of host cells. Probiotics play an insecure and protective role against the colonization of intestinal pathogenic microbes and increase mucosal integrity by stimulating epithelial cells. Probiotics have innate capabilities in many ways, including receptor antagonism, receptor expression, binding and expression of adapter proteins, expression of negative regulatory signal molecules, induction of microRNAs, endotoxin tolerance, and ultimately secretion of immunomodulatory proteins, lipids, and metabolites to modulate the immune system. Probiotic bacteria can affect homeostasis, inflammation, and immunopathology through direct or indirect effects on signaling pathways as immunosuppressant or activators. Probiotics suppress inflammation by inhibiting various signaling pathways such as the nuclear factor‐κB (NF‐κβ) pathway, possibly related to alterations in mitogen‐activated protein kinases and pattern recognition receptors pathways. Probiotics can also inhibit the binding of lipopolysaccharides to the CD14 receptor, thereby reducing the overall activation of NF‐κβ and producing proinflammatory cytokines. Some effects of modulation by probiotics include cytokine production by epithelial cells, increased mucin secretion, increased activity of phagocytosis, and activation of T and natural killer T cells, stimulation of immunoglobulin A production and decreased T cell proliferation. Intestinal microbiota has a major impact on the systemic immune system. Specific microbiota controls the differentiation of cells in lamina propria, in which Th17 cells secrete interleukin 17. The presence of Th17 and Treg cells in the small intestine is associated with intestinal microbiota, with the preferential Treg differentiation and the absence of Th17 cells, possibly reflecting alterations in the lamina propria cytokines and the intestinal gut microbiota. Abstract : Probiotics play an insecure and protective role against the colonization of intestinal pathogenic microbes and increase mucosal integrity by stimulating epithelial cells. Intestinal microbiota has a major impact on the systemic immune system. Specific microbiota controls the differentiation of cells in lamina propria, in which Th17 cells secrete interleukin 17. The presence of Th17 and Treg cells in the small intestine is associated with intestinal microbiota, with the preferential Treg differentiation and the absence of Th17 cells, possibly reflecting alterations in the lamina propria cytokines and the intestinal gut microbiota.